Dust and flour aeroallergen exposure in flour mills and bakeries. - Nieuwenhuijsen, M J (1994)
As part of an epidemiological study among workers exposed to flour total dust and flour aeroallergen concentrations were measured with personal samplers over a workshift in three large bakeries and four flour mills and packing stations. In the bakeries geometric means for total dust concentrations ranged from 0.4 mg/m3 in the bread wrapping area up to 6.4 mg/m3 at the dough brake. The flour aeroallergen concentrations ranged from 45.5 micrograms/m3 in the bread wrapping area up to 252.0 micrograms/m3 in the confectionary area. In the flour mills and packing stations the concentrations were higher with geometric means for total dust ranging from 0.5 mg/m3 in the office up to 16.9 mg/m3 for hygiene workers in an old mill. The flour aeroallergen concentrations ranged from 101.5 micrograms/m3 for transport workers up to 1728.2 micrograms/m3 for hygiene workers. The relation between total dust and flour aeroallergen concentrations varied for different areas and depended on the use of products other than flour.